A Combined Method For The Analysis Of Mine Ventilation Networks - S. Sarac (The Southern African Institute of Mining and Metallurgy, 2000)
Solving ventilation networks of natural splitting is a basic problem in mine ventilation. Several mathematical techniques are used to solve this problem. This paper proposes a new method which combines the advantages of both classical Hardy Cross method and unconstrained optimization techniques. The trials carried out on model networks have shown that the method offers some facilities in the analysis of mine ventilation networks. Keywords: Ventilation network analysis, Hardy Cross method, Steepest Descent method.